JAM’UL QUR’AN MASA KHULAFA ALRASYIDIN DAN SETELAH KHULAFA ALRASYIDIN - Inayatul Aisye; Indah Suci (CV. Adiba Aisha Amira, 2022)
Jam'ul Qur'an means collecting the sheets of the Qur'an that are in various containers such as date palms, stone plates and others collected in one place. There are two factors in the codification of the Qur'an. First, it was driven by the large number of Qur'an memorizers who died in the Yamamah war against Musailamah Al Kazzab which occurred during the time of Kahalifah Abu Bakr Siddik, Second; the occurrence of disputes between Muslims in reading the Qur'an. This led to disputes between one people and another and Caliph Usman bin Affan took the initiative to make it into one type of reading to unite the people. The purpose of the codified Qur'an is to unite the Qur'an that is scattered from one sheet and from all the memorization of friends before death picks them up so that they can be passed on to the next generation.